2019
DOI: 10.1111/1756-185x.13655
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and patterns of malignancies in a multi‐ethnic cohort of rheumatoid arthritis patients

Abstract: Aim This study was undertaken to determine the incidence and patterns of malignancies in rheumatoid arthritis (RA) patients in our cohort. Methods Between 2001 and 2013, we analyzed 1117 patients in the prospective Tan Tock Seng Hospital (TTSH) RA Registry. Patients who developed malignancies after the onset of RA were identified from this registry. Age‐ and sex‐adjusted standardized incidence ratios (SIRs) were calculated to compare observed to expected numbers of malignancies based on data from the Singapore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…RA is a chronic inflammatory autoimmune disease. Studies have shown that patients with rheumatoid arthritis have an increased risk of cancer [ 2 5 , 39 ]. The long-term chronic inflammatory microenvironment, the secretion of immunosuppressive factors such as IL-10, abnormal autoimmune response, and the use of immunosuppressive drugs have led to frequent tumor-like symptoms and paraneoplastic syndromes in RA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RA is a chronic inflammatory autoimmune disease. Studies have shown that patients with rheumatoid arthritis have an increased risk of cancer [ 2 5 , 39 ]. The long-term chronic inflammatory microenvironment, the secretion of immunosuppressive factors such as IL-10, abnormal autoimmune response, and the use of immunosuppressive drugs have led to frequent tumor-like symptoms and paraneoplastic syndromes in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that chronic inflammation caused by RA can induce malignant transformation of cells, and long-existing inflammatory mediators form a microenvironment that promotes cell mutagenesis and activates oncogenes [ 2 ]. The abnormal activation and proliferation of T lymphocytes, coupled with the frequent use of immunosuppressive drugs in RA patients, and autoimmune dysfunction affect the immune surveillance function and easily lead to immune escape, all of which increase the risk of tumors in RA patients [ 2 5 ]. In long-term clinical practice, we have found that RA patients are prone to increase in CA125 [ 6 , 7 ], especially in middle-aged and elderly women with high disease activity.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with RA are predisposed to a higher risk for malignancy [2][3][4][5][6][7]. It remains not entirely clear if the increased risk of malignancy is primarily related to the pathogenesis of the disease or due to the immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a systemic autoimmune disease, estimated to affect approximately 0.5% to 1% of population [1]. Patients with RA are predisposed to an increased risk for malignancy, especially malignant lymphomas [2][3][4][5][6][7], lung cancers [5,6] and non-melanoma skin cancer [7]. Higher mortality was associated with the presence of cancer, varied by stage of malignancy [8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this patient had been taking methotrexate for several years as treatment for rheumatoid arthritis. The resulting immunocompromised state might have exacerbated the persistent inflammation, possibly contributing to the development of PSCCE (10).…”
Section: Discussionmentioning
confidence: 99%